Phosphoenolpyruvate carboxylase and phosphoenolpyruvate carboxylase kinase isoenzymes play an important role in the filling and quality of Arabidopsis thaliana seed - Feria, Ana B (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 The Authors. Published by Elsevier Masson SAS.. All rights reserved.